Inocybe caryicola (Inocybaceae, Agaricales), a new species from Yunnan, China - Bi, Rongqian; Qu, Hua; Li, Ling; Zhao, Changlin; Ge, Zai-Wei (Phytotaxa, 2025)
Inocybe caryicola, a new species associated with Carya illinoinensis and discovered in Yunnan province, China, is described based on morphological characteristics and phylogenetic analyses. Inocybe caryicola is distinctly characterized by the pileus of young basidiomata with an obvious cortina, relatively small basidiospores that are angular to polygonal and have 11–13 distinct nodules, 2- or 4-spored basidia, and the presence of subclavate cauloparacystidia. This study provides a detailed description of the new species, photographs of the basidiomata, as well as microscopic images of the basidiospores under light microscopy (LM) and basidiospores under scanning electron microscopy (SEM). Molecular phylogenetic analyses based on ITS, LSU, and rpb2 show that Inocybe caryicola forms a highly supported clade, which is sister to the clade jointly formed by I. chondrospora and I. kuberae.